Bond strength of adhesive cements to root canal dentin tested with a novel pull-out approach - Ebert, Johannes; Leyer, Andrea; Günther, Oliver; Lohbauer, Ulrich; Petschelt, Anselm; Frankenberger, Roland; Roggendorf, Matthias Johannes (Journal of Endodontics, 2011)
Introduction: A novel approach to the pull-out test using silica-coated and silanized steel spreaders was designed to avoid influence from the post-cement interface. In this study, this test was applied to compare the post retention of adhesive versus conventional cements. Methods: Canals of 90 single-rooted human teeth were prepared to size 60 taper.02; trimmed to an 8-mm root canal length; irrigated with 40% citric acid, 3% NaOCl, and 70% ethanol; and randomly divided into 9 groups (n = 10). Steel spreaders (size 55, taper.02) were silica coated and silanized with the Rocatec system (3M-Espe, Seefeld, Germany), except for a control group using GCem, and cemented with one of these adhesive luting materials (RelyX Unicem [3M-Espe], Clearfil SA Cement [Kuraray Medical, Okayama, Japan], Bifix SE [Voco GmbH, Cuxhaven, Germany], NX3 [Kerr, Orange, CA], GCem [GC Corp, Tokyo, Japan], or SmartCem2 [Dentsply De Trey GmbH, Konstanz, Germany]) or conventional cements (Hoffmann's cement [Hoffmann Dental Manufaktur GmbH, Berlin, Germany] or Ketac Cem [3M-Espe]). After storage in distilled water (24 h/37°C), the spreaders were pulled out in a universal testing machine at a crosshead speed of 2 mm/min. Results: The failure mode was cohesive or adhesive at the cement-dentin interface in more than 80% of the experimental samples (control group: adhesive to the post: 9/10 samples). Adhesive luting materials retained posts better than conventional cements (t test, P <.001) but with a wide range in variation. RelyX Unicem displayed significantly higher values except when compared with Bifix SE and Clearfil SA (analysis of variance/Student-Newman-Keuls, P <.05). NX3, SmartCem2, and GCem showed no significant differences to Hoffmann's cement and Ketac Cem. Conclusions: The novel pull-out approach served well in testing the bond strength of different cements to root canal dentin. The bonding effectiveness of adhesive cements varied significantly and was material specific. Copyright © 2011 American Association of Endodontists.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive luting; conventional cementation; endodontic posts; pull-out resistance; Rocatec; self-adhesive cements